2020
DOI: 10.3390/vaccines8040599
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Seroprevalence Boost in the Pediatric and Adolescent Population of Florence (Italy) as a Preventive Strategy for Congenital Rubella Syndrome (CRS)

Abstract: Background: Despite the availability of an effective vaccine since the 1970s, rubella disease and, importantly, congenital rubella syndrome (CRS) remain a public health concern. The aim of this study was to analyze the rubella seroprevalence in the children population of the province of Florence and compare the obtained results to a previous survey conducted in 2005–2006. Methods: A qualitative measurement of anti-rubella antibodies was performed on 165 sera using the enzyme-linked immunosorbent Assay (ELISA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thanks to the UVV program (set up in 2008 in Tuscany), the varicella cases successfully dropped from 350 notified cases/100,000 in 1992 to 20 notified cases/100,000 in 2018 [17]. Unlike the other seroprevalence studies carried out in the same sample of measles [19], rubella [20] and hepatitis B [21], in which no cases were reported to the surveillance system of infectious diseases, seven notifications were observed for varicella. Since varicella infections are rarely asymptomatic, the clinical diagnosis is generally easy [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the UVV program (set up in 2008 in Tuscany), the varicella cases successfully dropped from 350 notified cases/100,000 in 1992 to 20 notified cases/100,000 in 2018 [17]. Unlike the other seroprevalence studies carried out in the same sample of measles [19], rubella [20] and hepatitis B [21], in which no cases were reported to the surveillance system of infectious diseases, seven notifications were observed for varicella. Since varicella infections are rarely asymptomatic, the clinical diagnosis is generally easy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Varicella seroprevalence investigation is part of a wider seroepidemiological project that has been carried out by the Department of Health Sciences of the University of Florence since 2017, aiming to assess varicella seroprevalence in the same sample population used for measles [ 19 ], rubella [ 20 ], hepatitis A and B [ 21 ] and tetanus surveillance. The overall goal of this study was to investigate the varicella seroprevalence in a pediatric and adolescent (1–18 years) population of the province of Florence and to relate the obtained data with the anamnestic and vaccination status of each subject, with particular attention to the varicella notifications.…”
Section: Introductionmentioning
confidence: 99%
“…18–20 A study from Florence (Italy) also showed no significant difference in rubella antibodies between genders. 21 However, there is only one study that reported a significant difference between genders, possibly due to different definitions of cutoff values for seronegative and seropositive rubella antibodies. 22 Our study also revealed a decrease in the GMC of rubella IgG over time, and antibody levels were statistically significant with respect to the time since the last vaccination ( P < .001), which is similar to the results of another study.…”
Section: Discussionmentioning
confidence: 99%
“…This hepatitis A seroprevalence analysis is part of a wider seroepidemiological project carried out by the Department of Health Sciences of the University of Florence, started in 2017. This study included the seroprevalence investigation of other vaccine-preventable disease such as Hepatitis B [ 10 ], Measles [ 11 ], Rubella [ 12 ] and Varicella [ 13 ]. Blood samples collection took place at the blood sampling center of Meyer Children’s Hospital (Florence, Italy) in the period December 2017–April 2018.…”
Section: Methodsmentioning
confidence: 99%